Odpowiedzi

Najlepsza Odpowiedź!
2010-03-25T14:11:36+01:00
A)
{3x-4y=14
{-2x+7y=-18|:(-2)

3x-4y=14
x=9+3,5y

3(9+3,5y)-4y=14
27+10,5y-4y=14
6,5y=-13
y=-2

x=9+3,5*(-2)
x=9-7
x=2


b)
{4x-2y=6
{3x+6y=12|:3

4x-2y=6
x=4-2y

4(4-2y)-2y=6
16-8y-2y=6
-10y=-10
y=1

x=4-2*1
x=4-2
x=2


c)
{3y+5x=0
{3x+2y=4|:3

3y+5x=0
x=1⅓-⅔y

3y+5(1⅓-⅔y)=0
3y+6⅔-3⅓y=0
-⅓y=-6⅔
y=20

x=1⅓-⅔*20
x=1⅓-13⅓
x=-12


d)
{7x-y+17=0
{5x+6y=8|:5

7x-y=-17
x=1,6-1,2y

7(1,6-1,2y)-y=-17
11,2-8,4y-y=8
-9,4y=-3,2
y=16/47

x=1,6-1,2*16/47
x=1,6-96/235
x=1⁹/₄₇


e)
{2x+5y=6|:2
{3x-4y=2

x=3-2,5y
3(3-2,5y)-4y=2
9-7,5y-4y=2
-11,5y=-7
y=14/23

x=3-2,5*14/23
x=3-1¹²/₂₃
x=1¹¹/₂₃

f)
{y-2x=6
{y+3=x

y=6+2x
6+2x+3=x
x=-9

y=6+2*(-9)
y=6-18
y=-12
3 5 3